Case report: miller fisher syndrome associated with systemic lupus erythematosus activity - Oliveira, Caique; Wiesentainer , Maiara; Alflen , Paulla; Bisinotto, Karla; Corte, Douglas (Headache Medicine, 2024)
Introduction Miller Fisher Syndrome (MFS) is characterized by the classic triad of ophthalmoplegia, ataxia, and areflexia, representing a rare variant of Guillain-Barré Syndrome (GBS). Systemic lupus erythematosus (SLE) is a complex autoimmune disease that can affect multiple systems, including the nervous system. The coexistence of MFS and SLE is rare, posing significant diagnostic and therapeutical challenges. Objective To describe a case of MFS associated with SLE activity. Case Report A 33-year-old Caucasian woman diagnosed with SLE since 2019, with irregular treatment, was referred to University Hospital for investigation of ascending progressive muscle weakness without evidence of prior infections, occurring concurrently with SLE activity. Neurological examination revealed flaccid tetraparesis associated with right ophthalmoparesis, horizontal nystagmus, bilateral photoreactive mydriasis, trunk ataxia, and global hyporeflexia. Cerebrospinal fluid (CSF) analysis showed albuminocytological dissociation (protein 85 mg/dL and cells 6/mm³). Cranial computed tomography and magnetic resonance imaging (brain and cervical spine) did not reveal acute lesions. She underwent a 5-day course of Intravenous Immunoglobulin (IVIG) and experienced complete recovery of neurological symptoms after two weeks. Conclusion This case highlights the rare coexistence of MFS during SLE activity, emphasizing complete remission of neurological symptoms following the early intervention with Intravenous Immunoglobulin (IVIG). Keywords: Miller Fisher Syndrome, Systemic Lupus Erythematosus, Guillain-Barre syndrome.